Vocal size exaggeration may have contributed to the origins of vocalic complexity. (3rd January 2022) - Pisanski, Katarzyna; Anikin, Andrey; Reby, David
Abstract : Vocal tract elongation, which uniformly lowers vocal tract resonances (formant frequencies) in animal vocalizations, has evolved independently in several vertebrate groups as a means for vocalizers to exaggerate their apparent body size. Here, we propose that smaller speech-like articulatory movements that alter only individual formants can serve a similar yet less energetically costly size-exaggerating function. To test this, we examine whether uneven formant spacing alters the perceived body size of vocalizers in synthesized human vowels and animal calls. Among six synthetic vowel patterns, those characterized by the lowest first and second formant (the vowel /u/ as in 'boot') are consistently perceived as produced by the largest vocalizer. Crucially, lowering only one or two formants in animal-like calls also conveys the impression of a larger body size, and lowering the second and third formants simultaneously exaggerates perceived size to a similar extent as rescaling all formants. As the articulatory movements required for individual formant shifts are minor compared to full vocal tract extension, they represent a rapid and energetically efficient mechanism for acoustic size exaggeration. We suggest that, by favouring the evolution of uneven formant patterns in vocal communication, this deceptive strategy may have contributed to the origins of the phonemic diversification required for articulated speech. This article is part of the theme issue 'Voice modulation: from origin and mechanism to social impact (Part II)'.